Assessment of Patient-Reported Outcomes in Patients With Anal Squamous-Cell Cancer Undergoing Combined Modality Therapy. Issue 12 (5th September 2022) - Taylor, James P.; Wei, Iris H.; Joshua Smith, J.; Tin, Amy L.; Aiken, Nate; Vickers, Andrew J.; Romesser, Paul B.; Crane, Christopher H.; Widmar, Maria; Nash, Garrett M.; Weiser, Martin R.; Paty, Philip B.; et al.
Abstract : BACKGROUND: There is limited knowledge on long-term bowel, sexual, and urinary function after combined modality therapy for anal squamous-cell cancer. OBJECTIVE: This study aimed to evaluate long-term changes in patients treated with combined modality. DESIGN: This was a retrospective study of prospectively collected patient-reported outcome surveys. SETTING: This study was conducted at a single institution. PATIENTS: There were 143 patients with stage I to III anal cancer who were treated with chemoradiation and had completed the survey. MAIN OUTCOME MEASURES: This study included patient-reported outcomes reflecting bowel, sexual, and urinary function. RESULTS: Thirty-nine percent of patients had major low anterior resection syndrome at baseline. Major low anterior resection syndrome remained stable (38%; 95% CI, 31%–46%) with no change over time (OR 0.95; 95% CI, 0.74–1.21; p = 0.7). Higher rates of major low anterior resection syndrome were observed for patients who had major low anterior resection syndrome at baseline (OR 20.7; 95% CI 4.70–91.3; p < 0.001) and for females (OR 2.14; 95% CI, 1.01–4.56; p = 0.047). On 5-point scales, we saw a nonsignificant increased level of sexual arousal during sexual activity after therapy for women (β for 1 year = 0.15; 95% CI, –0.01 to 0.32; p = 0.072) and nonsignificant decreased confidence in getting and keeping an erection after therapy for men (β for 1 year = –0.33; 95% CI, –0.66 to 0.00; p = 0.053). LIMITATIONS: This was a single-institution study and only patients who answered the questionnaire were included in the study. CONCLUSIONS: A significant proportion of patients have major low anterior resection syndrome at baseline and after successful treatment for anal cancer. Having major low anterior resection syndrome at baseline was the biggest predictor of having major low anterior resection syndrome after treatment. Bowel, sexual, and urinary function did not improve over time up to 2 years after end of treatment. Physicians should counsel their patients before treatment that baseline poor bowel function is a risk factor for posttreatment bowel dysfunction. See Video Abstract at http://links.lww.com/DCR/C29 . EVALUACIÓN DE LOS RESULTADOS INFORMADOS POR LOS PACIENTES CON CÁNCER ANAL DE CÉLULAS ESCAMOSAS QUE SE SOMETEN A UNA TERAPIA DE MODALIDAD COMBINADA: ANTECEDENTES: Existe un conocimiento limitado sobre la función intestinal, sexual y urinaria a largo plazo después de la terapia de modalidad combinada para el cáncer anal de células escamosas. OBJETIVO: Evaluar los cambios a largo plazo en la función intestinal, sexual y urinaria en pacientes tratados con modalidad combinada. DISEÑO: Este fue un estudio retrospectivo de encuestas de resultados informadas por pacientes recolectadas prospectivamente. ESCENARIO: Institución única. PACIENTES: Fueron 143 pacientes con cáncer anal en estadio I–III que fueron tratados con quimiorradiación y completaron la encuesta. PRINCIPALES MEDIDAS DE RESULTADO: Resultados reportados por el paciente que reflejan la función intestinal, sexual, y urinaria. RESULTADOS: Treinta y nueve por ciento de los pacientes tenían puntajes importantes de síndrome de resección anterior bajo al inicio del estudio. Las puntuaciones del síndrome de resección anterior baja mayor permanecieron estables (38 %; IC del 95%: 31 %, 46 %) sin cambios con el tiempo (OR 0, 95, IC del 95%: 0, 74, 1, 21, p = 0, 7). Se observaron tasas más altas de puntuaciones del síndrome de resección anterior baja mayor para los pacientes que tenían puntuaciones del síndrome de resección anterior baja mayor desde el inicio (OR 20, 7; IC del 95%: 4, 70; 91, 3, p < 0, 001) y para las mujeres (OR 2, 14; IC del 95%: 1, 01, 4, 56; p = 0, 047). En escalas de 5 puntos, observamos un aumento no significativo del nivel de excitación sexual durante la actividad sexual después de la terapia para las mujeres (β durante 1 año = 0, 15; IC del 95%: -0, 01, 0, 32; p = 0, 072) y una disminución no significativa de la confianza en lograr y mantener una erección después de la terapia para hombres (β para 1 año = -0, 33; IC del 95%: -0, 66, 0, 00; p = 0, 053). LIMITACIONES: Este es un estudio de una sola institución. Solo se incluyeron en el estudio los pacientes que contestaron el cuestionario. CONCLUSIONES: Una proporción significativa de pacientes tienen puntajes de síndrome de resección anterior muy bajos al inicio del estudio y después de un tratamiento exitoso para el cáncer anal. Tener puntajes de síndrome de resección anterior bajos importantes al inicio del estudio fue el predictor más importante de tener puntajes de síndrome de resección anterior bajos importantes después del tratamiento. La función intestinal, sexual y urinaria no mejoró con el tiempo hasta 2 años después de finalizar el tratamiento. Los médicos deben aconsejar a sus pacientes antes del tratamiento que la mala función intestinal inicial es un factor de riesgo para la disfunción intestinal posterior al tratamiento. Consulte Video Resumen en http://links.lww.com/DCR/C29 . (Traducción—Dr. Yolanda Colorado )